The Effect of Traditional Game-Based Learning Media on Students’ Motivation and Participation in Physical Education at an Elementary School in Parepare - Marhani Marhani (International Journal of Humanities, Education, and Social Sciences, 2026)
Although the use of traditional games in physical education has received increasing attention in prior studies, research specifically examining their effect on both students’ motivation and active participation at the elementary school level in Parepare remains limited. This study aims to analyze the effect of traditional game-based learning media on students’ motivation and participation in physical education learning. A quantitative approach was employed using a quasi-experimental design with a nonequivalent control group model, involving 58 fifth-grade students selected through purposive sampling. The study was conducted in November 2025 at SDIT Ashabul Kahfi Parepare. Data were collected using a motivation questionnaire and structured observation sheets to measure student participation, and were analyzed using descriptive statistics and an independent samples t-test. The findings indicate a significant difference between the experimental and control groups: students who participated in learning activities using traditional games demonstrated higher motivation scores (M = 86.45) than those in the conventional learning group (M = 74.28). In addition, the level of active participation in the experimental group reached 89%, exceeding that of the control group (73%). These results contribute to the theoretical development of constructivist learning theory and active learning concepts by demonstrating the effectiveness of culturally relevant and engaging learning media. The study concludes that the integration of traditional games plays a crucial role in enhancing students’ motivation and participation in physical education, and recommends that physical education teachers adopt traditional game-based strategies as an alternative instructional approach. The implications include theoretical contributions to the growing literature on culturally responsive pedagogy in physical education and practical recommendations for schools to incorporate local cultural resources into learning activities. Furthermore, this study highlights opportunities for future research on the long-term impacts of traditional game integration and its influence on students’ physical fitness and social skills development.